A new digital bathymetric model of the world's oceans. Issue 8 (4th August 2015) - Weatherall, Pauline; Marks, K. M.; Jakobsson, Martin; Schmitt, Thierry; Tani, Shin; Arndt, Jan Erik; Rovere, Marzia; Chayes, Dale; Ferrini, Vicki; Wigley, Rochelle
Abstract: General Bathymetric Chart of the Oceans (GEBCO) has released the GEBCO_2014 grid, a new digital bathymetric model of the world ocean floor merged with land topography from publicly available digital elevation models. GEBCO_2014 has a grid spacing of 30 arc sec and updates the 2010 release (GEBCO_08) by incorporating new versions of regional bathymetric compilations from the International Bathymetric Chart of the Arctic Ocean, the International Bathymetric Chart of the Southern Ocean, the Baltic Sea Bathymetry Database, and data from the European Marine Observation and Data network bathymetry portal, among other data sources. Approximately 33% of ocean grid cells (not area) have been updated in GEBCO_2014 from the previous version, including both new interpolated depth values and added soundings. These updates include large amounts of multibeam data collected using modern equipment and navigation techniques, improving portrayed details of the world ocean floor. Of all nonland grid cells in GEBCO_2014, approximately 18% are based on bathymetric control data, i.e., primarily multibeam and single‐beam soundings or preprepared grids which may contain some interpolated values. The GEBCO_2014 grid has a mean and median depth of 3897 m and 3441 m, respectively. Hypsometric analysis reveals that 50% of the Earth's surface is composed of seafloor located 3200 m below mean sea level and that ~900 ship years of surveying would be needed to obtain complete multibeam coverage of the world's oceans. Key Points: GEBCO_2014, a digital global bathymetric model, is documented Thirty‐three percent of ocean grid cells have been updated from previous version Updated regional bathymetric compilations and other data incorporated